Unravelling Venom: Histopathological Changes After Snake Envenomation - Prasanth, Saravana; Rani , Smitha; V Menon, Pooja; Patel M C, Sapna (Journal of Forensic Medicine and Toxicology, 2026)
This case study presents a detailed clinical account of a patient suffering from Snakebite envenoming (SBE), outlining the clinical symptoms, diagnostic approaches, focusing on histopathological changes seen in such cases. Histopathological changes following snake envenomation are crucial for understanding the mechanisms of venom toxicity and developing effective therapeutic interventions. These changes vary depending on the snake species, the venom composition, and the envenomation site. Locally, venom induces tissue necrosis, myonecrosis, and haemorrhage often accompanied by inflammation, vascular damage, and edema. In skeletal muscles, histological observations frequently reveal degenera tion, loss of myofibers, and infiltration of inflammatory cells. Venom’s proteolytic enzymes—particularly metallopro teinases—contribute significantly to the degradation of tissue and basement membranes, further exacerbating damage. Systemically, snake venom can target multiple organs, with histopathological changes observed in the liver, kidney, heart, and lungs. Hepatic injury often manifests as hepatocyte degeneration, sinusoidal congestion, and vacuolization. Renal histopathology shows acute tubular necrosis, glomerular damage, and interstitial inflammation—often a result of ven om-induced hemolysis, myoglobinuria, or direct nephrotoxic effects. Cardiotoxicity is evidenced by myocardial fiber damage, interstitial oedema, and inflammatory cell infiltration. Additionally, in pulmonary tissues, venom can lead to alveolar hemorrhage, congestion, and inflammation. These changes are further amplified by coagulopathies, dissem inated intravascular coagulation (DIC), and immune responses triggered by venom components. Understanding the histopathological changes not only highlights the mechanisms of venom toxicity but also aids in the development of antivenoms and adjunct therapies aimed at mitigating local and systemic damage.
Keywords: Envenomation; Hemorrhage; Pathology; Cause of death